EVALUATION OF ROAD DAMAGE AND MAINTENANCE USING THE PAVEMENT CONDITION INDEX METHOD CASE STUDY ON JALAN SUKAHAJI - MAJA - Khaeril Anwar Nawawi; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2024)
The road is a facility that is very important for the community to achieve a desired goal, for that we need a road that is safe and comfortable for its use. Road damage often occurs every year, especially on roads that are often traversed by vehicles with a lot of volume (congested ) and vehicles that are heavily loaded (overloaded) such as on the Sukahaji – Maja road, which causes the speed of users to slow down (drop) and have an impact on reducing population mobility and the economy of the surrounding community. The purpose of this research is to determine the level of road damage using the Payment Condition Index (PCI) method. The survey method or PCI refers to ASTM D6433 (Standard Practice for Roads and Parking Lots Pavement Condition Surveys). Pavement Condition Index (PCI) is a road pavement condition assessment system based on the type, level, and extent of damage that occurs and can be used as a reference in maintenance efforts. This PCI value has a range of 0 to 100 with the criteria of excellent, very good, good, fair, poor, very poor, and failed. Based on the analysis using the PCI method, for the type of damage that occurs on the Sukahaji-Maja road for the flexible pavement/asphalt type, 6 types of damage occur, namely alligator cracking, striping, grain release, collapse, vanished, and potholes. In Table 4.2 the average PCI value obtained is then entered into the parameters as in the table so that the road can be categorized as damaged, namely Poor (Damaged). So this road needs to be included in a road improvement program on an ongoing basis.